1993
DOI: 10.3109/01913129309041299
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrastructural Study of Six Cases of Chronic Active C Hepatitis. A Comparison with Chronic Active B Hepatitis

Abstract: Liver biopsies from six patients affected by chronic active hepatitis (CAH) induced by hepatitis C virus (HCV) have been investigated ultrastructurally and their features compared with those of five cases of CAH induced by hepatitis B virus (HBV). Clusters of deeply packed nuclear inclusions (18 to 22 nm in diameter) were found in patients with HCV-CAH. They were irregularly round and ill-delimited. These inclusions were distinct from the regular round and well-delimited nuclear inclusions associated with HBV.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Liver biopsies were randomly collected at the end time of ischemia and reperfusion. Specimens underwent technical procedures for electron microscopy as described [12]. Briefly, they were fixed in 2% glutaraldehyde (4°C, pH 7.4), postfixed in 1% osmium tetroxide, and embedded in an Epon-araldite mixture.…”
Section: Groupsmentioning
confidence: 99%
“…Liver biopsies were randomly collected at the end time of ischemia and reperfusion. Specimens underwent technical procedures for electron microscopy as described [12]. Briefly, they were fixed in 2% glutaraldehyde (4°C, pH 7.4), postfixed in 1% osmium tetroxide, and embedded in an Epon-araldite mixture.…”
Section: Groupsmentioning
confidence: 99%
“…Ultrastructural studies are essential to analyse the fine structure of liver biopsy specimens for signs of pathogenesis. Previous studies have identified several histologic features in the liver of patients with chronic hepatitis C (CHC), 5 including intranuclear inclusions of densely packed, irregular, round, and heterogeneous particles 6 ; focally or diffusely dilated endoplasmic reticulum (ER) 6 ; and irregularly shaped mitochondria. However, no consensus findings on hepatocellular organelles in patients with CHC have been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%